DIRECT ACTING ANTIVIRALS IN HEPATITIS C INFECTION: DEVELOPING A PERSONALISED MODEL OF CARE - El-Sherif, Omar (School of Medicine, 2018)
Summary Hepatitis C infection (HCV) is a major global health problem. The HCV treatment landscape has changed beyond recognition in a few short years. The development of HCV direct acting antiviral therapy (DAA) has occurred extremely rapidly from the approval of the first-generation protease inhibitors telaprevir and boceprevir that were combined with peginterferon (IFN) and ribavirin, to all oral single tablet interferon free combination such as ledipasvir-sofosbuvir in less than 4 years. Despite the dramatic success of DAA development, challenges remain on the path to cure. The aim of this thesis is to generate data related to (i) the clinical pharmacokinetics (PK) of DAA therapy in real-world patients and (ii) DAA treatment outcomes in special populations. PK observational studies were designed to provide quantitative data and develop population PK (PopPK) models for the first-generation protease inhibitor telaprevir, and the second- generation NS5A inhibitor ledipasvir. DAA treatment outcomes and predictors of improvement in liver function in patients with decompensated cirrhosis were investigated through an integrated analysis of clinical trials of sofosbuvir based IFN-free DAA therapy. Treatment outcomes in persons who inject drugs were assessed in a large retrospective study of 1000 patients treated with peginterferon and ribavirin. The clinical PK studies of telaprevir demonstrated significant inter-individual variability in telaprevir concentrations and exposure, with lower drug exposure in patients with cirrhosis. A one-compartment Pop PK model with first-order absorption and linear elimination best described telaprevir PK with population clearance 32.4L/hr (CV ~ 20%) and volume of distribution 257L. Weight and fibrosis stage were significant covariates for telaprevir exposure. A highly sensitive, reliable and reproducible bioanalytical method for the simultaneous quantification of sofosbuvir, GS-331007, ledipasvir, daclatasvir and simeprevir was developed and validated as part of this thesis. This method was used to study ledipasvir PK in a cohort of 314 patients with decompensated cirrhosis treated with ledipasvir-sofosbuvir and ribavirin. There was no effect of Child-Pugh-Turcot (CPT) stage on ledipasvir concentrations, and in multivariate analysis, proton pump inhibitor (PPI) use was the most significant predictor of ledipasvir concentrations. Mean ledipasvir trough concentrations were approximately 20% lower in patients on low dose PPI therapy. Relative bioavailability was 34% lower in patients on low dose PPI therapy based on PopPK modelling. Patients with decompensated cirrhosis can now be considered for DAA therapy. However, patient selection remains a challenge. An integrated analysis of clinical trial data from 620 patients with decompensated cirrhosis was performed. Patients who achieved SVR12 had a significantly higher change of achieving compensated liver status (CPT class A) post treatment (HR 2.1, 95% CI 1.0 – 4.3 p = 0.04). A five point BEAAA score (BMI, encephalopathy, ascites, ALT and albumin) was developed to predict patients that would benefit from treatment. A BEAAA score of 4-5 was associated with a HR of 52.28 (95% CI 15.2 – 179.7) of treatment benefit, and may be used to select patients for treatment. In the study of outcomes in persons who inject drugs (PWID), treatment outcomes and adherence in recent and former PWID were similar to non-drug users, supporting the inclusion of these marginalised patients in national treatment programmes. The WHO target of HCV elimination may be achievable provided treatment moves towards a more personalised model of care to maximise treatment outcomes in all populations.
Keywords: HIV